Ru / graphene carbon nano composite material as well as preparation method and application thereof
Through the Ru/graphene carbon nanocomposite in the nitrobenzene hydrogenation reduction reaction, the graphene-type structure loading Ru nanoparticles is used to adjust the ammonia borane water to explain the release of hydrogen, which solves the problems of reaction safety hazards and catalyst deactivation in traditional methods. , improves the reaction rate and stability, and achieves a low-cost and efficient catalytic effect.
Patent Information
- Application Number
- CN202411325947.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2024-12-27
AI Technical Summary
The prior art has safety hazards and slow reaction rates during the hydrogenation reduction process of nitrobenzene, the catalyst is prone to deactivate, and the preparation method of carbon-supported metal nanocomposites leads to disorderly dispersion of metal nanoparticles, affecting catalytic performance.
Ru/graphene carbon nanocomposite is used to form a ruthenium-based metal organic frame material through solvent heat treatment, and the graphene-type structure is calcined to form Ru nanoparticles to regulate the rate of hydrogen release by ammonia borane water, and the reaction is carried out in series to increase nitrobenzene Safety and efficiency of hydrogenation reduction reaction.
The rate and safety of nitrobenzene hydrogenation reduction reaction under mild conditions are achieved, the stability and reaction efficiency of the catalyst are enhanced, and the materials are easy to prepare and cost are low.
Smart Images

Figure CN119186556A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic nanomaterials, and in particular to a Ru / graphene carbon nanocomposite material and a preparation method and application thereof. Background Art
[0002] Nitrobenzene compounds are chemical substances that are harmful to human health and the environment. Therefore, the hydrogenation reduction of nitrobenzene into a non-toxic and useful chemical substance aniline is of great significance.
[0003] Hydrogen is required as raw material in the hydrogenation reduction conversion process of nitrobenzene, and the traditional method directly uses hydrogen as the hydrogen source. This method requires high temperature and high pressure reaction conditions, which not only poses a safety hazard to the reaction, but also has a slow hydrogenation reaction rate, which is not conducive to the hydrogenation reduction conversion of nitrobenzene.
[0004] In order to solve the above technical problems, the prior art proposes to improve the hydrogenation reaction rate by screening catalysts, such as copper catalysts and precious metal catalysts. Among them, although copper catalysts can improve the hydrogenation reaction rate to a certain extent, they have poor anti-poisoning performance and a very small amount of sulfide can poison and deactivate the catalyst, such as the Cu / SiO2 catalyst disclosed in the prior art CN1504259A. Although precious metal catalysts can also improve the hydrogenation reaction rate to a certain extent, they are prone to side reactions, local overheating and coking and deactivation, such as the Pd / hydrotalcite catalyst disclosed in the prior art with DOI number 10.1016 / j.apcata.2008.10.044. Therefore, it is necessary to provide a catalyst that can improve the hydrogenation reaction rate in the nitrobenzene hydrogenation reduction conversion process under relatively mild reaction conditions. To this end, the present invention provides a Ru / graphene carbon nanocomposite material and its preparation method and application. Summary of the invention
[0005] In order to overcome the potential safety hazard of directly using hydrogen as a hydrogen source in the above-mentioned traditional method, the present invention attempts to replace the hydrogen source to provide a hydrogen source that can safely carry out the hydrogenation reduction reaction of nitrobenzene compounds. In the process of screening hydrogen sources, the present invention finds that ammonia borane is a potential excellent hydrogen storage material with high hydrogen content, good water solubility and stability, and the Ru / C graphene carbon nanocomposite material obtained by the present invention catalyzes the hydrolysis reaction of ammonia borane to slowly release hydrogen, which can provide a hydrogen source for subsequent reactions and has high safety. Therefore, the present invention attempts to improve the reaction safety and reaction efficiency in the subsequent hydrogenation reduction conversion process of nitrobenzene compounds by connecting the two reactions of hydrogen release by ammonia borane hydrolysis and hydrogenation reduction of nitrobenzene compounds in series.
[0006] However, when the present invention connects the two reactions of ammonia borane hydrolysis and hydrogenation reduction of nitrobenzene compounds in series, it is found that the hydrogen release rate in the previous ammonia borane hydrolysis and hydrogenation reaction has a great influence on the hydrogenation reaction rate in the subsequent nitrobenzene compound hydrogenation reduction reaction. Therefore, the present invention attempts to adjust the hydrogen release rate in the ammonia borane hydrolysis and hydrogenation reaction by adjusting the amount of catalyst, thereby achieving the adjustment of the subsequent nitrobenzene compound hydrogenation reduction reaction rate.
[0007] Moreover, in the process of screening catalyst materials, the present invention considers that the composite material formed by carbon material supported metal nanoparticles in the prior art has good catalytic performance, so the present invention attempts to use the composite material formed by carbon material supported metal nanoparticles for catalytic regulation of the release rate of hydrogen in the ammonia borane hydrolysis hydrogenation reaction, so as to realize regulating the hydrogenation reaction rate in the subsequent nitrobenzene compound hydrogenation reduction reaction. However, the prior art generally prefabricates carbon materials first when preparing carbon supported metal nanocomposites, and then disperses the prefabricated metal nanoparticles on the obtained carbon material, thereby obtaining the composite material. In the composite material formed by this method, the metal nanoparticles are randomly and disorderly dispersed on the carbon carrier, which makes the necessary interaction between the carrier carbon atoms and the metal nano atoms lack, thereby affecting the performance of the material catalytic performance. For this reason, the present invention proposes to use metal organic framework as a matrix, and realizes the composite of carbon material and metal by calcining the metal organic framework, so the present invention provides a Ru / graphene carbon nanocomposite material and its preparation method and application.
[0008] The Ru / graphene carbon nanocomposite material and its preparation method and application are achieved by the following technical solutions:
[0009] The first object of the present invention is to provide a method for preparing a Ru / graphene carbon nanocomposite material, comprising the following steps:
[0010] Step 1: Using a soluble ruthenium salt as a ruthenium source, and using 2,5-di(1-imidazole)pyridine and 4,4'-diphenyldicarboxylic acid as ligands, a solvent thermal treatment is performed to allow the ruthenium ions provided by the soluble ruthenium salt to chelate with the ligands to form a ruthenium-based metal organic framework material.
[0011] It should be noted that the present invention takes into account that the Ru ions in the MOFs material form a three-dimensional polymer structure with the carboxyl-containing ligands and the nitrogen-containing ligands, and a graphene-type polymer structure can be formed during the calcination and carbonization process. Therefore, ruthenium-based metal organic framework materials are preferably used as the raw materials for preparing carbon-loaded metal nanocomposites, so as to achieve uniform loading of metal ruthenium nanoparticles on graphene carbon to form Ru / graphene carbon nanocomposites.
[0012] When constructing ruthenium-based metal organic framework materials, in order to increase the solubility of the raw materials and improve the yield of the precursor product Ru-MOFs, in some preferred embodiments of the present invention, a soluble ruthenium salt is used as a ruthenium source to increase the content of ruthenium ions for constructing ruthenium-based metal organic framework materials. In addition, the present invention takes into account the factors of improving reaction efficiency and not introducing other elements such as S to cause impurities in the target product. In other preferred embodiments of the present invention, the soluble ruthenium salt used is RuCl3.
[0013] When constructing ruthenium-based metal organic framework materials, the present invention takes into account the factors of coordination between carboxyl groups and imidazole N and metal ruthenium. Therefore, in some preferred embodiments of the present invention, 2,5-di(1-imidazole)pyridine and 4,4'-diphenyldicarboxylic acid are preferably used together as ligands to form a coordination polymer to achieve the construction of a ruthenium-based metal organic framework material having a three-dimensional framework polymerization structure.
[0014] In order to ensure that the soluble ruthenium salt and ligand used can chelate and construct a ruthenium-based metal organic framework material during the solvothermal reaction, in some preferred embodiments of the present invention, the molar ratio of the soluble ruthenium salt, 2,5-di(1-imidazole)pyridine and 4,4'-diphenyldicarboxylic acid used is 0.8-1.2:1:1.
[0015] In order to ensure that the soluble ruthenium salt and the ligand used can fully react, it is necessary to make the soluble ruthenium salt and the ligand fully dispersed or dissolved in the solvent used in the solvothermal reaction. Therefore, in some preferred embodiments of the present invention, during the solvothermal treatment, the solvent used is preferably a mixed solvent of acetonitrile and water, and the volume ratio of acetonitrile to water is 1:2 to 4. In some preferred embodiments of the present invention, the amount ratio of the solvent used to the soluble ruthenium salt is 15mL to 25mL: 1mmol, so as to obtain Ru-MOFs with good crystal form and high yield.
[0016] In order to further ensure that the soluble ruthenium salt and the ligand can fully react during the solvothermal reaction, in some preferred embodiments of the present invention, the temperature of the solvothermal treatment is 110°C to 130°C to ensure that a high yield of Ru-MOFs is obtained within this temperature range. And in order to further ensure that the reaction can be fully achieved within the above temperature range, in some preferred embodiments of the present invention, the time of the solvothermal treatment is 48h to 96h.
[0017] Step 2: calcining the ruthenium-based metal organic framework material in a protective gas atmosphere to obtain a Ru / graphene carbon nanocomposite material composed of metal ruthenium nanoparticles and graphene carbon.
[0018] It should be noted that during the calcination process of the ruthenium-based metal organic framework material of the present invention, the organic framework structure in the ruthenium-based metal organic framework material collapses, the organic components therein are calcined to become gaseous oxides and volatilize away, while the carbon element therein remains and forms a carbon layer of a graphene-type structure, that is, graphene carbon is formed, and the formed graphene carbon basically maintains the structural shape of the coordination polymer. At the same time, the metal ions in the ruthenium-based metal organic framework material are in-situ reduced to metal ruthenium nanoparticles during the calcination process, and are evenly distributed on the graphene carbon, thereby obtaining a Ru / graphene carbon nanocomposite material composed of metal ruthenium nanoparticles and graphene carbon.
[0019] It should be emphasized that the carbon in the material obtained after calcination of the present invention does not exist in the form of general amorphous carbon, but in the form of graphene structure. The regular arrangement of graphene carbon is not only conducive to the high dispersion of metal ruthenium nanoparticles, but also to the Ru / graphene carbon nanocomposite material with uniform component distribution, which is conducive to ensuring the stability of material performance. In addition, the graphene carbon has a fluffy structure, high porosity, and large specific surface area. Its accumulation forms pores, so that the Ru / graphene carbon nanocomposite material obtained by the present invention has a strong adsorption capacity for the substrate molecules of the catalytic reaction, and can adsorb the substrate molecules on the graphene network, close to the active reaction center of the metal Ru nanoparticles, so that it is easy to react, thereby enhancing the catalytic reaction ability of the Ru / graphene carbon nanocomposite material.
[0020] In order to ensure that the carbon in the material obtained after calcination does not exist in the form of general amorphous carbon, but in the form of graphene structure, in some preferred embodiments of the present invention, the temperature of the calcination treatment is 300℃~800℃. And the present invention found in the process of exploration that the higher the calcination temperature, the carboxyl and N elements in the precursor MOFs will be oxidized into CO2 and NO2 gases and volatilized, so the final result is amorphous carbon. Therefore, in order to prevent the graphene carbon layer from being destroyed during the calcination process, so as to ensure that the material obtained after calcination exists in the form of graphene structure, in other preferred embodiments of the present invention, the temperature of the calcination treatment is 300℃~400℃. In other preferred embodiments of the present invention, the preferred calcination temperature is 350℃, and at this temperature, a graphene carbon layer with complete structure and best performance can be formed, which can be used as the optimal carrier of ruthenium nanoparticles.
[0021] The present invention has found in the process of exploration that if the calcination time is too short, the precursor will be insufficiently calcined, the Ru-MOFs framework will not be broken enough, and the Ru 2+If the ion reduction is insufficient, the number of Ru nanoparticles is small; if the calcination time is too long, the polymer structure in MOFs is broken, resulting in an incomplete graphene carbon structure of the product. Therefore, in order to further ensure that the carbon can be composited with the metal Ru nanoparticles in the form of graphene carbon within the above temperature range, in some other preferred embodiments of the present invention, the calcination time is 1h to 3h. In some other preferred embodiments of the present invention, the calcination time is more preferably 2h.
[0022] In some preferred embodiments of the present invention, the protective gas atmosphere during the calcination treatment is nitrogen. If no protective gas is added, Ru will become RuO2 under the action of oxygen during the calcination process. The target product will contain RuO2 impurities.
[0023] The second object of the present invention is to provide a Ru / graphene carbon nanocomposite material prepared by the above preparation method.
[0024] The third object of the present invention is to provide an application of the Ru / graphene carbon nanocomposite material in catalyzing the hydrolysis and hydrogenation reaction of ammonia borane and the tandem hydrogenation and reduction reaction of nitrobenzene.
[0025] It should be noted that, when the Ru / graphene carbon nanocomposite material is used to improve the hydrogenation reduction reaction of nitrobenzene, the two reactions of hydrogen release by hydrolysis of ammonia borane and hydrogenation reduction of nitrobenzene compound are connected in series for reaction, the hydrogen released by hydrolysis of ammonia borane is used as the hydrogen source for the hydrogenation reduction reaction of nitrobenzene, and the Ru / graphene carbon nanocomposite material is used as a catalyst, without the need to provide additional hydrogen, thereby achieving the improvement of the reaction safety and product yield of the hydrogenation reduction reaction process of nitrobenzene, and at the same time, the stability of the reaction can be increased, the reaction efficiency can be improved, and the composite material is easy to prepare and has low cost.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention uses a soluble ruthenium salt as a ruthenium source, and uses 2,5-di(1-imidazole)pyridine and 4,4'-diphenyldicarboxylic acid as ligands. The ruthenium ions provided by the soluble ruthenium salt are chelated with the ligands to form a ruthenium-based metal organic framework material through solvent thermal treatment. The ruthenium-based metal organic framework material obtained by calcination collapses the organic framework structure, and the organic components therein become gaseous oxides after calcination and volatilize away, while the carbon elements therein remain and form carbon with a graphene-type structure, that is, graphene carbon is formed, and the formed graphene carbon basically maintains the shape of a coordination polymer. At the same time, the metal ions in the ruthenium-based metal organic framework material are in-situ reduced to metal ruthenium nanoparticles during the calcination process, and are evenly distributed on the graphene carbon, thereby obtaining a Ru / graphene carbon nanocomposite material composed of metal ruthenium nanoparticles and graphene carbon.
[0028] In the Ru / graphene carbon nanocomposite material obtained by the present invention, since the graphene carbon has a fluffy structure, high porosity and large specific surface area, it is accumulated to form pores, so that the Ru / graphene carbon nanocomposite material obtained by the present invention has a strong adsorption capacity for substrate molecules of the catalytic reaction, and can adsorb the substrate molecules on the graphene network, close to the active reaction center of the metal Ru nanoparticles, so that the reaction is easy to occur, thereby enhancing the catalytic reaction ability of the Ru / graphene carbon nanocomposite material.
[0029] The present invention connects two reactions of hydrogen release by hydrolysis of ammonia borane and hydrogenation reduction of nitrobenzene compounds in series to react, uses hydrogen released by hydrolysis of ammonia borane as a hydrogen source for hydrogenation reduction of nitrobenzene, and uses the Ru / graphene carbon nanocomposite material as a catalyst, thereby improving the reaction safety in the hydrogenation reduction reaction process of nitrobenzene, increasing the reaction stability, and improving the reaction efficiency. The composite material is easy to prepare and has low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic diagram of the preparation process of the present invention.
[0031] Figure 2 This is the crystal structure diagram of Ru-MOFs of Comparative Example 1.
[0032] Figure 3 XRD spectra of Ru / C of Example 1 and Ru-MOFs of Comparative Example 1.
[0033] Figure 4 Raman spectra of Ru / C of Example 1 and Ru-MOFs of Comparative Example 1.
[0034] Figure 5 This is the transmission electron microscope image of Ru / C in Example 1.
[0035] Figure 6 This is a high-resolution transmission electron microscope of Ru / C in Example 1.
[0036] Figure 7 BET diagrams of Ru / C of Example 1 and Ru-MOFs of Comparative Example 1.
[0037] Figure 8 The pore size distribution diagram of Ru / C of Example 1 and Ru-MOFs of Comparative Example 1.
[0038] Fig. 9 This is a graph showing the hydrogen release performance when the materials obtained in Comparative Example 1 and Examples 1 to 5 are used as catalysts.
[0039] Fig.10This is a graph showing the hydrogen release performance when the materials obtained in Examples 6 to 8 are used as catalysts.
[0040] Fig.11 The results of the performance test on the catalytic release of hydrogen from ammonia borane at different Ru / C dosages in Example 1.
[0041] Fig.12 These are the test results of the effect of the initial concentration of ammonia borane on the catalytic performance of the Ru / C-catalyzed ammonia borane hydrolysis and hydrogenation reaction in Example 1.
[0042] Fig.13 The test results show the effect of the reaction temperature of the catalytic reaction on the catalytic performance of the Ru / C-catalyzed ammonia borane hydrolysis and hydrogenation reaction in Example 1.
[0043] Fig.14 These are the test results of the effect of solution pH on the catalytic performance of the Ru / C-catalyzed ammonia borane hydrolysis and hydrogenation reaction of Example 1.
[0044] Fig.15 The test results of reaction rate of the catalytic hydrolysis and hydrogenation of ammonia borane and the hydrogenation reduction of p-nitrophenol.
[0045] Fig.16 These are the test results of the reaction rate of the catalytic hydrolysis and hydrogenation of ammonia borane followed by the hydrogenation reduction of p-aminophenol.
[0046] Fig.17 These are the test results of the reaction rate of the catalytic hydrolysis and hydrogenation of ammonia borane followed by the hydrogenation reduction of p-methylaminobenzene.
[0047] Fig.18 These are the test results of the cycle performance of the Ru / C-catalyzed ammonia borane hydrolysis and hydrogenation reaction of Example 1.
[0048] Fig.19 The XRD spectra of Ru / C in Example 1 before and after the catalytic ammonia borane hydrolysis hydrogenation reaction cycle performance test. DETAILED DESCRIPTION
[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. It should be noted that, for the convenience of description, in the following embodiments of the present invention, the ligand 2,5-di(1-imidazole)pyridine is referred to as bip, and the ligand 4,4'-diphenyldicarboxylic acid is referred to as bpdc.
[0050] Example 1
[0051] See also Figure 1 This embodiment provides a Ru / graphene carbon nanocomposite material, which is prepared by the following steps:
[0052] Step 1, preparation of ruthenium-based metal organic framework materials:
[0053] 1) Mix acetonitrile and deionized water in a volume ratio of 1:3 to obtain a reaction solvent, and take 20 mL for later use.
[0054] 2) 1.0 mmol of RuCl3, 1.0 mmol of 2,5-di(1-imidazole)pyridine and 1.0 mmol of 4,4'-diphenyldicarboxylic acid were placed in 20 mL of the above reaction solvent and mixed to obtain a mixture.
[0055] 4) The mixture obtained above was transferred to a reaction kettle, reacted at 120° C. for 72 h, cooled to room temperature, filtered, washed and dried to obtain a ruthenium-based metal organic framework material.
[0056] Step 2, calcination treatment:
[0057] Under nitrogen atmosphere, the Ru-MOFs obtained in the above step 1 were calcined at 350° C. for 2 h to obtain a Ru / graphene carbon nanocomposite material, which was recorded as Ru / C.
[0058] Example 2
[0059] This embodiment provides a Ru / graphene carbon nanocomposite material, and the difference between this embodiment and embodiment 1 is only that:
[0060] In this example, the calcination temperature is 300° C., and the Ru / graphene carbon nanocomposite material obtained in this example is recorded as Ru / C (300° C.).
[0061] Example 3
[0062] This embodiment provides a Ru / graphene carbon nanocomposite material, and the difference between this embodiment and embodiment 1 is only that:
[0063] In this example, the calcination temperature is 400° C., and the Ru / graphene carbon nanocomposite material obtained in this example is recorded as Ru / C (400° C.).
[0064] Example 4
[0065] This embodiment provides a Ru / graphene carbon nanocomposite material, and the difference between this embodiment and embodiment 1 is only that:
[0066] In this example, the calcination temperature is 450° C., and the Ru / graphene carbon nanocomposite material obtained in this example is recorded as Ru / C (450° C.).
[0067] Example 5
[0068] This embodiment provides a Ru / graphene carbon nanocomposite material, and the difference between this embodiment and embodiment 1 is only that:
[0069] In this example, the calcination temperature is 500° C., and the Ru / graphene carbon nanocomposite material obtained in this example is recorded as Ru / C (500° C.).
[0070] Example 6
[0071] This embodiment provides a Ru / graphene carbon nanocomposite material, and the difference between this embodiment and embodiment 1 is only that:
[0072] In this example, the calcination temperature is 600° C., and the Ru / graphene carbon nanocomposite material obtained in this example is recorded as Ru / C (600° C.).
[0073] Example 7
[0074] This embodiment provides a Ru / graphene carbon nanocomposite material, and the difference between this embodiment and embodiment 1 is only that:
[0075] In this example, the calcination temperature is 700° C., and the Ru / graphene carbon nanocomposite material obtained in this example is recorded as Ru / C (700° C.).
[0076] Example 8
[0077] This embodiment provides a Ru / graphene carbon nanocomposite material, and the difference between this embodiment and embodiment 1 is only that:
[0078] In this example, the calcination temperature is 500° C., and the Ru / graphene carbon nanocomposite material obtained in this example is recorded as Ru / C (800° C.).
[0079] Comparative Example 1
[0080] This comparative example provides a ruthenium-based metal organic framework material, which is prepared by the following steps:
[0081] 1) Mix acetonitrile and deionized water in a volume ratio of 1:3 to obtain a reaction solvent, and take 20 mL for later use.
[0082] 2) 1.0 mmol of RuCl3, 1.0 mmol of 2,5-di(1-imidazole)pyridine and 1.0 mmol of 4,4'-diphenyldicarboxylic acid were placed in 20 mL of the above reaction solvent and mixed to obtain a mixture.
[0083] 4) The mixture obtained above was transferred to a reactor, reacted at 120° C. for 72 h, cooled to room temperature, filtered, washed and dried to obtain a ruthenium-based metal organic framework material, referred to as Ru-MOFs.
[0084] That is, the only difference between this comparative example and Example 1 is that this comparative example does not undergo calcination treatment.
[0085] Experimental Section
[0086] (I) Structural test analysis
[0087] The present invention tests and analyzes the structure of Ru-MOFs of Comparative Example 1, and obtains its structure as follows: Figure 2 shown.
[0088] Figure 2 This is the crystal structure diagram of Ru-MOFs of Comparative Example 1. It can be seen that each asymmetric unit of Ru-MOFs is composed of four crystallographically independent Ru(II) cations, two bip ligands, four deprotonated bpdc ligands, four coordinated water molecules and five free lattice acetonitrile molecules.
[0089] Among them, only one of the five acetonitrile molecules is a complete molecule, and the other four acetonitrile molecules are incompletely occupied. The carbon atom is 0.5 (C79, C80, C81, C82, C85, C86, C87, C88). The coordination mode of 4,4'-biphenyldicarboxylic acid with Ru(II) is: the coordination mode of the two carboxylic acid groups in bpdc is monodentate. The four Ru(II) metal centers all have a similar tetrahedral four-coordinate environment, which is composed of two carboxylic acid oxygen atoms in the bpdc ligand, a nitrogen atom in the bip ligand, and an oxygen atom coordinated with water and Ru(II). The two imidazole rings in the bip ligand almost form a conjugated plane with the middle pyridine ring. The two benzene rings in the bpdc ligand are tilted to a certain extent. During the crystal formation process, Ru(III) changes from +3 valence to +2 valence. The coordination number of Ru(II) is 4, which is relatively rare in Ru complexes.
[0090] (ii) XRD test
[0091] The present invention performs XRD tests on the Ru / C of Example 1 and the Ru-MOFs of Comparative Example 1, and the test results are as follows: Figure 3 shown. Figure 3The XRD spectra of Ru / C of Example 1 and Ru-MOFs of Comparative Example 1 show that the XRD spectra of Ru / C show all the characteristic diffraction of Ru nanoparticles. The peaks of Ru nanoparticles are 38.4°, 42.2°, 44.0°, 58.3°, 69.4°, 78.4°, and the corresponding lattice planes are (100), (002), (101), (102), (110), (103) (PDF#06-0663), and the data obtained are consistent with the literature report (Small 2022, 18, 1544-1558). In addition to the diffraction peaks of Ru nanoparticles, no other peaks are observed in the XRD spectrum of Ru / C. In the Ru / C prepared by the present invention, Ru exists in the form of pure ruthenium nanoparticles, indicating that the present invention successfully constructs Ru / graphene carbon nanocomposites.
[0092] (III) Raman spectroscopy test
[0093] The present invention performs Raman spectroscopy tests on the Ru / C of Example 1 and the Ru-MOFs of Comparative Example 1, and the test results are as follows: Figure 4 shown.
[0094] Figure 4 The Raman spectra of Ru / C of Example 1 and Ru-MOFs of Comparative Example 1 show that the Ru / C obtained after calcination has obvious D band and G band peaks, and the DG band intensity ratio (I D / I G ) is a commonly used indicator reflecting the graphitization degree and defect density of carbon materials. D / I G =0.9, confirming that the obtained material is a typical graphene-based carbon with a large number of oxygen-containing -COOH functional groups, indicating the successful synthesis of Ru / C graphene carbon nanocomposites.
[0095] (IV) Transmission electron microscopy test
[0096] The present invention conducted a transmission electron microscope test on the Ru / C of Example 1, and the test results are as follows: Figure 5 shown.
[0097] Figure 5 The transmission electron microscope image of Ru / C of Example 1 shows that the material obtained in Example 1 is a wavy sheet with a wrinkled structure, which is a characteristic of graphene-based carbon. Gas expansion during the calcination and carbonization of MOFs produces a large number of pores, and the graphene carbon sheet is formed by the collapse of the framework structure of MOFs. The morphology of Ru / C is a structure similar to that of graphene mesh, and ruthenium nanoparticles are distributed on its nodes. Ruthenium nanoparticles of about 20nm are spherical particles and are evenly distributed on the surface of graphene-based carbon.
[0098] (V) High-resolution transmission electron microscopy test
[0099] The present invention conducted a high-resolution transmission electron microscopy test on the Ru / C of Example 1, and the test results are as follows: Figure 6 shown.
[0100] Figure 6 The high-resolution transmission electron microscopy image of Ru / C in Example 1 shows that the lattice spacing d=0.214 nm in the material obtained in Example 1 is consistent with the (002) plane of Ru nanoparticles (JCPDS#06-0663). This indicates that the Ru / C nanocomposite material has been successfully obtained and the Ru nanoparticles are well distributed in the graphene-based carbon.
[0101] (VI) BET test
[0102] The present invention carried out BET test on Ru / C of Example 1 and Ru-MOFs of Comparative Example 1, and the test results are as follows: Figure 7 shown.
[0103] Figure 7 The BET diagrams of Ru / C of Example 1 and Ru-MOFs of Comparative Example 1 show that the two curves of Ru-MOFs and Ru / C present type IV isotherms, accompanied by hysteresis loops, indicating that both Ru-MOFs and Ru / graphene carbon nanocomposites are mesoporous structures. The specific surface area of Ru-MOFs is 41.1845 m 2 / g. After calcination, the specific surface area increases to 55.5278m 2 / g. This indicates that the adsorption capacity of the Ru / C graphene carbon nanocomposite material is improved after it is formed. As the N2 absorption rate increases, more pores are formed on the material. The pores generate cavities, and the increase in their number is conducive to the hydrogen separation reaction of ammonia borane water. Therefore, the catalytic performance of the obtained material is enhanced.
[0104] (VII) Pore size distribution test
[0105] The present invention conducted a pore size distribution test on the Ru / C of Example 1 and the Ru-MOFs of Comparative Example 1, and the test results are as follows: Figure 8 shown.
[0106] Figure 8 The pore size distribution diagram of Ru / C of Example 1 and Ru-MOFs of Comparative Example 1 shows that the pore size of the Ru / C graphene carbon nanocomposite material is 2 nm to 5 nm.
[0107] (VIII) Catalytic Hydrolysis and Hydrogenation Reaction of Ammonia Borane
[0108] 1) Effect of calcination temperature on the catalytic performance of the catalyst for the hydrolysis and hydrogenation reaction of ammonia borane
[0109] The present invention uses the composite materials obtained in Examples 1 to 8 as catalysts, and uses the Ru-MOFs of Comparative Example 1 as a control group, and uses the following method to test to explore the effect of calcination temperature on the hydrolysis and hydrogenation reaction of ammonia borane catalyzed by the catalyst:
[0110] Catalytic hydrolysis of ammonia borane to release hydrogen is carried out in a three-necked flask connected to a gas burette. The gas burette can be used to measure the amount of hydrogen produced during the hydrolysis reaction. In the present invention, 0.5 mmol of ammonia borane and 15 mg of Ru / C catalyst are added to a container containing 5 mL of ultrapure water, and then the two solutions are mixed, stirred for reaction, and the volume of hydrogen is measured every 2 minutes. The test results are as follows: Fig. 9 and Fig.10 shown.
[0111] Fig. 9 This is a graph showing the hydrogen release performance when the materials obtained in Comparative Example 1 and Examples 1 to 5 are used as catalysts. It can be seen that the material calcined at 350° C. has the best performance in catalyzing the hydrogen release of ammonia borane.
[0112] Fig.10 This is a graph showing the hydrogen release performance of the materials obtained in Examples 6 to 8 as catalysts. It can be seen that at higher calcination temperatures, the hydrogen release performance of the obtained materials catalyzing ammonia borane decreases.
[0113] 2) Effect of catalyst dosage on the catalytic performance of the catalyst in the hydrolysis and hydrogenation reaction of ammonia borane
[0114] The present invention uses the Ru / C of Example 1 as a catalyst and adopts the following method to conduct a test to explore the effect of the catalyst dosage on the catalyst-catalyzed ammonia borane hydrolysis and hydrogenation reaction:
[0115] The test method and test conditions are as follows: 0.5 mmol of ammonia borane is dissolved in 5 mL of ultrapure water to obtain solution 1. Then 5 mg, 8 mg, 10 mg, 12 mg, and 15 mg of Ru / C of Example 1 are respectively dissolved in 5 mL of ultrapure water to obtain solution 2. The mixed solutions 1 and 2 are reacted and the hydrogen volume is tested every 2 minutes. The test results are as follows: Fig.11 shown.
[0116] Fig.11 is the relationship between the amount of catalyst used and the volume of hydrogen released by hydrolysis of ammonia borane, Fig.11 It can be seen that the optimal catalyst dosage is 15 mg.
[0117] 3) Effect of the initial concentration of ammonia borane on the catalytic performance of the catalyst for the hydrolysis and hydrogenation reaction of ammonia borane
[0118] The present invention uses the Ru / C of Example 1 as a catalyst and adopts the following method to conduct a test to explore the effect of the initial concentration of ammonia borane on the catalyst-catalyzed hydrolysis and hydrogenation reaction of ammonia borane:
[0119] The test method and test conditions are:
[0120] Prepare ammonia borane solutions with initial concentrations of 25mM, 50mM, 75mM, 100mM and 125mM, respectively, and label them as solution 3. Dissolve 15mg of Ru / C in 5mL of ultrapure water to obtain solution 4. Take 5mL of solution 3 and add it to solution 4 to start the reaction. Test the hydrogen volume every 2min. Where mM means mmol·L -1 . And the test results are as follows Fig.12 shown.
[0121] Fig.12 is the test result of the effect of the initial concentration of ammonia borane on the catalytic performance of the Ru / C catalyzed ammonia borane hydrolysis and hydrogenation reaction in Example 1, Fig.12 It can be seen that the optimal initial concentration of ammonia borane is 25 mM, i.e. 25 mmol·L -1 .
[0122] 4) Effect of reaction temperature on the catalytic performance of the catalyst in the hydrolysis and hydrogenation reaction of ammonia borane
[0123] The present invention uses the Ru / C of Example 1 as a catalyst and adopts the following method to conduct a test to explore the effect of the reaction temperature of the catalytic reaction on the hydrolysis and hydrogenation reaction of ammonia borane catalyzed by the catalyst:
[0124] The test method and test conditions are as follows: 0.5 mmol of ammonia borane is dissolved in 5 mL of ultrapure water to obtain solution 5. 15 mg of Ru / C is dissolved in 5 mL of ultrapure water to obtain solution 6. Solutions 5 and 6 are mixed and stirred for reaction. The reaction temperature is changed to 298K, 303K, 308K, 313K and 318K respectively, and the hydrogen volume is tested every 2 minutes. The test results are as follows: Fig.13 shown.
[0125] Fig.13 The test results of the effect of the reaction temperature of the catalytic reaction on the catalytic performance of the Ru / C-catalyzed ammonia borane hydrolysis and hydrogenation reaction of Example 1 are as follows: Fig.13 It can be seen that when reacting at 318K, the obtained material has the best effect in catalyzing the dehydrogenation of ammonia borane.
[0126] 5) Effect of solution pH on the catalytic performance of the catalyst for the hydrolysis and hydrogenation reaction of ammonia borane
[0127] In order to explore the effect of solution pH on the hydrolysis and hydrogenation reaction of ammonia borane, the present invention uses Ru / C prepared in Example 1 as a catalyst to test the hydrogen release effect in solutions with different pH values by the following test method:
[0128] Dissolve 0.5 mmol of ammonia borane in 5 mL of ultrapure water to obtain solution 7. Dissolve 15 mg of Ru / C in 5 mL of ultrapure water to obtain solution 8. Mix solutions 7 and 8 and stir to react. Change the pH value of the solution and test the hydrogen volume every 2 minutes.
[0129] Adjustment of solution pH: Take PBS buffer solution with pH=2-12 and add it to the reaction solution. Use 0.1 mol·L -1 HCl solution and 0.1 mol·L -1 The pH value of each solution was adjusted by adding NaOH solution, and the pH value of each solution was measured by a pH meter to adjust the solution pH to 7, 8, 10, 12 and 14 respectively. The test results are as follows Fig.14 shown.
[0130] Fig.14 The test results of the effect of solution pH on the catalytic performance of the Ru / C-catalyzed ammonia borane hydrolysis and hydrogenation reaction in Example 1 are as follows: Fig.14 It can be seen that when the pH value of the solution is between 7 and 8, the catalytic effect of ammonia borane on hydrogen release is the best.
[0131] (IX) Catalytic Hydrolysis of Ammonia Borane and Hydrogenation of Nitrobenzene in Series
[0132] The present invention uses Ru / C prepared in Example 1 as a catalyst to explore its catalytic effect on the catalytic hydrolysis and hydrogenation of ammonia borane and the tandem hydrogenation and reduction reaction of nitrobenzene, and the test method is as follows.
[0133] 1) Catalytic hydrolysis of ammonia borane and hydrogenation and reduction of p-nitrophenol
[0134] Weigh 0.5 mmol of p-nitrophenol and dissolve it in 10 mL of ultrapure water to obtain solution 9. Weigh 0.5 mmol of ammonia borane and 15 mg of catalyst Ru / C respectively and add them to 5 mL of a mixed solvent of equal volumes of methanol / H2O to form a mixed solution 10. Mix solutions 9 and 10 and stir to react at 50°C. Use a UV-vis spectrophotometer to monitor the formation of the product and the change in the reaction rate, wherein the peak positions are monitored: p-nitrophenol, 400 nm; p-aminophenol, 292 nm.
[0135] And the test results are as follows Fig.15 shown.
[0136] Fig.15The reaction rate test results of the reaction of catalyzing the hydrolysis and hydrogenation of ammonia borane and the hydrogenation reduction of p-nitrophenol are shown. It can be seen that the catalyst Ru / C catalyzes the hydrolysis and hydrogenation of ammonia borane and the hydrogenation of p-nitrophenol to obtain p-aminophenol, and the reaction can be completed within 40 seconds, and the reaction yield is almost 100%.
[0137] 2) Catalytic hydrolysis of ammonia borane and hydrogenation of p-nitroaniline in series
[0138] The present invention also replaces the p-nitrophenol in the above-mentioned catalytic ammonia borane hydrolysis hydrogenation series p-nitrophenol hydrogenation reduction reaction with p-nitroaniline, and then uses the above-mentioned method to test the p-nitroaniline hydrogenation reaction catalyzed by the catalyst Ru / C. The generation of the product and the change in the reaction rate are monitored by a UV-vis spectrophotometer, wherein the monitoring peak positions are: p-nitroaniline, 370nm, p-phenylenediamine, 240nm. And the test results are as follows Fig.16 shown.
[0139] Fig.16 The reaction rate test results of the catalytic hydrolysis and hydrogenation of ammonia borane and the hydrogenation reduction of p-aminophenol show that the catalyst Ru / C can complete the reaction of the hydrolysis and hydrogenation of ammonia borane and the hydrogenation of p-nitroaniline to obtain p-phenylenediamine within 140 seconds, and the reaction yield can reach 95%.
[0140] 3) Catalytic hydrolysis of ammonia borane and hydrogenation of p-nitrotoluene in series
[0141] The present invention also replaces the p-nitrophenol in the above-mentioned catalytic ammonia borane hydrolysis hydrogenation series p-nitrophenol hydrogenation reduction reaction with p-nitrotoluene, and then uses the above-mentioned method to test the catalyst Ru / C catalyzed p-nitrotoluene hydrogenation reaction. The generation of the product and the change in the reaction rate are monitored by a UV-vis spectrophotometer, wherein the monitoring peak positions are: p-nitrotoluene, 285nm, p-aminotoluene, 232nm. And the test results are as follows: Fig.17 shown.
[0142] Fig.17 The reaction rate test results of the reaction of catalyzing the hydrolysis and hydrogenation of ammonia borane in series with the hydrogenation reduction of p-methylaminobenzene show that the catalyst Ru / C can complete the reaction of catalyzing the hydrolysis and hydrogenation of ammonia borane in series with the hydrogenation of p-nitrotoluene to obtain p-aminotoluene within 120 seconds, and the reaction yield can reach 90%.
[0143] (X) Cyclic performance test of Ru / C catalyzed ammonia borane hydrolysis and hydrogenation reaction
[0144] At the beginning of the first reaction cycle, 15 mg of Ru / C catalyst was dissolved in 5 mL of ultrapure water to obtain solution 11. Ammonia borane was dissolved in ultrapure water to obtain a concentration of 200 mmol·L -15 mL of ammonia borane aqueous solution was taken as solution 12. Solution 11 was added to solution 12 and stirred at a reaction temperature of 298 K. The volume of hydrogen released was measured. After the reaction was completed, the reaction solution was filtered to obtain the Ru / C catalyst, which was dried and then dissolved in 5 mL of ultrapure water to obtain solution 13. Another 5 mL of the above-prepared solution with a concentration of 200 mmol·L -1 The ammonia borane aqueous solution is used as solution 14. Solution 13 is added to solution 14 for a second cycle reaction, and the volume of hydrogen released is measured. The catalyst is then filtered out, and the cycle reaction is repeated four times. The test results of the volume of hydrogen released during each cycle are as follows: Fig.18 shown.
[0145] Fig.18 This is the test result of the cyclic performance of the Ru / C catalyzed ammonia borane hydrolysis and hydrogenation reaction in Example 1. It can be seen that the Ru / graphene carbon composite material has stable performance in catalyzing ammonia borane hydrolysis and hydrogenation, good cyclicity, and can maintain catalytic activity after four cycle reactions.
[0146] The present invention also conducted XRD tests on the Ru / C of Example 1 before and after the catalytic ammonia borane hydrolysis hydrogenation reaction cycle performance test, and the test results are as follows: Fig.19 shown.
[0147] Fig.19 This is the XRD spectrum of Ru / C in Example 1 before and after the catalytic ammonia borane hydrolysis hydrogenation reaction cycle performance test. By comparing the XRD spectra before and after the catalyst is used, it can be seen that the XRD is almost unchanged, indicating that the composition and structure of the catalyst remain unchanged and has good catalytic stability.
[0148] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a Ru / graphene carbon nanocomposite material, characterized in that: The following steps are involved: A soluble ruthenium salt is used as a ruthenium source, and 2,5-di(1-imidazole)pyridine and 4,4'-diphenyldicarboxylic acid are used as ligands to perform a solvent thermal treatment, so that the ruthenium ions provided by the soluble ruthenium salt are chelated with the ligands to form a ruthenium-based metal organic framework material; The ruthenium-based metal organic framework material is calcined in a protective gas atmosphere to collapse the organic framework structure in the ruthenium-based metal organic framework material and form graphene carbon. The metal ions in the ruthenium-based metal organic framework material are in-situ reduced to metal ruthenium nanoparticles during the calcination process and are evenly distributed on the graphene carbon to form a Ru / graphene carbon nanocomposite material composed of metal ruthenium nanoparticles and graphene carbon.
2. The preparation method according to claim 1, characterized in that The calcination temperature is 300°C to 800°C.
3. The preparation method according to claim 2, characterized in that: The calcination temperature is 300°C to 400°C.
4. The preparation method according to claim 1, characterized in that: The soluble ruthenium salt is RuCl3.
5. The preparation method according to claim 1, characterized in that: The molar ratio of the soluble ruthenium salt, 2,5-di(1-imidazole)pyridine and 4,4'-diphenyldicarboxylic acid is 0.8-1.2:1:
1.
6. The preparation method according to claim 1, characterized in that: The temperature of the solvent thermal treatment is 110°C to 130°C.
7. The preparation method according to claim 1, characterized in that: During the solvent thermal treatment, the solvent used is a mixed solvent of acetonitrile and water in a volume ratio of 1:2 to 4.
8. The preparation method according to claim 1, characterized in that: The calcination treatment time is 1 h to 3 h.
9. A Ru / graphene carbon nanocomposite material prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the Ru / graphene carbon nanocomposite material according to claim 9 in catalyzing the hydrogenation reduction of nitrobenzene, characterized in that: The hydrogen released by the hydrolysis of ammonia borane is used as a hydrogen source for the hydrogenation reduction reaction of nitrobenzene, and the Ru / graphene carbon nanocomposite material is used as a catalyst.
